PELAYANAN PERNIKAHAN DI KANTOR URUSAN AGAMA KECAMATAN BANJARSARI KOTA SURAKARTA - Desi Rahmawati (Master of Public Administration, Universitas Slamet Riyadi, 2017)
This study was aimed to explore the marriage service at Religious Affairs atBanjarsari Sub District Surakarta City. The formulated research problemswere reviewed by five dimensions of services, i.e. dimensions of tangability,reliability, responsiveness, assurance and of empathy. Questionnaire wasused to collect the data. Qualitative data were collected by employingdocument study and interview indepth. One hundred respondents consistingof service users were interviewed. Research result indicated that the quality ofwork performance of the Religious Affairs Office at Banjarsari Sub DistrictSurakarta City seemed not satisfyng fully the service users. It is due to the factthat there was still existed the gap between what should be done by theemployees of the office and what it was expected by the service users. Theservice users percepted that the services given by the employees was notfully satisfied according to five measurement dimensions of service. Thehighest score of gap between the real service given by the employees on theone hand and the users’ perception as well as the users’ expectation was thedimension of tangability, followed by the dimensions of responsiveness,empathy, assurance and the last was dimension of reliability, respectively.Based on research result, it is recommended that there should be someefforts done by office related to the five dimensions for promoting betterservices in order to satisfy the users of the services.Key words : tangability, reliability, responsiveness, assurance, empathy.